THE EFFECT OF PERCEIVED BENEFIT, PERCEIVED RISK, PERFORMANCE EXPECTANCY, SOCIAL INFLUENCE AND HEDONIC MOTIVATION ON QRIS INTENTION USAGE IN PONTIANAK WITH CULTURE VALUES AS A MODERATION VARIABLE - Jeni, Jeni (Equator Journal of Management and Entrepreneurship (EJME), 2025)
This research is aims to examine the impact of perceived benefit, perceived risk, performance expectancy, social influence, and hedonic motivation on the intention to use QRIS in Pontianak, with culture values as a moderating variable. Using a quantitative survey method, the results show that perceived benefit, social influence, and hedonic motivation all have a positive and significant effect on the intention usage QRIS. Conversely, perceived risk has a negative and significant effect, while performance expectancy does not influence QRIS intention usage. Additionally, culture values do not moderate the relationships between performance expectancy and hedonic motivation on QRIS intention usage, but they do significantly moderate the relationships between perceived benefit, perceived risk, and social influence on QRIS usage intention